Succession of Digital Goods. A Comparative Legal Study - Fras, Mariusz (Review of European and Comparative Law, 2021)
The purpose of this article is to present possible solutions to the problem of access to digital contents left by a deceased user of Internet services under different European legal systems. Discussion of this issue from a comparative perspective will allow the drawing of general conclusions about the direction de lege lata in which European legislation is heading. In my opinion there should be dedicated legal provisons introduced into the polish civil code which would pertain to digital goods. This would also facilitate the harmonization of inheritance matters in a European perspective. Technological development requires amending the civil code to fit changing reality.